Hubungan Ukuran Kantor Akuntan Publik Dengan Opini Audit (Studi Pada Perusahaan Non Keuangan yang Terdaftar di BEI Tahun 2011-2012) - Martalina Kalincayo Purba; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
Financial Statements audited provide assurance to users of financial statements that the report has been fit for use as a basis for decision making. Audit quality provided by audit firm is important to provide assurance that the financial statements have been audited properly. This study aims to examine whether there is a relationship between the size of the audit firm with audit quality given. Audit firm size was measured using the total assets audited and total sales audited by audit firm during the year, while the audit quality is measured using the audit opinion provided by the firm. This study is a replication study of Li et al (2008).The population used is listed on the Stock Exchange the period 2011 to 2012, with a sample of non-financial companies that obtained by purposive sampling method. Processing of the data in this study using logistic regression. The results showed that there is a relationship between the size of the audit firm with audit quality, that the greater the size of the audit firm, the better the quality of a given audit.